19-fs pulse generated by supercontinuum compression. (10th January 2016) - Zhang 张, Hua-Qiang 华强; Wang 王, Peng 鹏; Liu 刘, Wen-Jun 文军; Yao 蕾, Yi-Lei 姚翳; Xu 徐, Zhi-Jing 志敬; Li 健, Jian 李
Abstract: Supercontinuum generation and compression in a length of 50-mm photonic crystal fiber with pulse of nanojoule energy are investigated theoretically and experimentally. Chirped mirror pair is used for dispersion compensation and pulse compression. Pulse characteristics are measured by frequency-resolved optical gating. And 19-fs pulse is generated.